2010
DOI: 10.1038/jp.2010.43
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal predictors of outcome in gastroschisis

Abstract: Objective: To identify perinatal risk variables predictive of outcome in gastroschisis.Study Design: Gastroschisis cases were collected over a 3-year period from a national database. Risk variables evaluated included gestational age (GA), birth weight, time of birth, admission illness severity (score for neonatal acute physiology-II, SNAP-II) score, and abdominal closure type. Mortality and survival outcomes were analyzed. Multivariate analyses were performed.Result: In all, 239 infants were survived (96%). SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…SNAP-II was initially developed to predict mortality of infants admitted to neonatal intensive care units [14]. Several studies have reported that SNAP-II is predictive of infant mortality for various conditions, including prematurity [15,35,36], congenital diaphragmatic hernia [37][38][39], gastroschisis [40], respiratory distress [41], and persistent pulmonary hypertension [42]. However, SNAP-II has also been shown to be predictive of brain abnormalities in the preterm population, specifically suppressed amplitude-integrated electroencephalographic activity [43], intraventricular hemorrhage [15,44], moderate to severe ventriculomegaly, and echodense lesions in white matter [15].…”
Section: Snap-ii Predicts Microstructural Development Of the Corticosmentioning
confidence: 99%
“…SNAP-II was initially developed to predict mortality of infants admitted to neonatal intensive care units [14]. Several studies have reported that SNAP-II is predictive of infant mortality for various conditions, including prematurity [15,35,36], congenital diaphragmatic hernia [37][38][39], gastroschisis [40], respiratory distress [41], and persistent pulmonary hypertension [42]. However, SNAP-II has also been shown to be predictive of brain abnormalities in the preterm population, specifically suppressed amplitude-integrated electroencephalographic activity [43], intraventricular hemorrhage [15,44], moderate to severe ventriculomegaly, and echodense lesions in white matter [15].…”
Section: Snap-ii Predicts Microstructural Development Of the Corticosmentioning
confidence: 99%
“…This finding may reflect the failure of these individual variables to enhance the predictive ability already encompassed by the GPS, a potentially stronger predictor of outcome. An examination of the individual risk attributes of SNAP-II suggests that its predictive ability is focused on the uncommon clinical scenario of the physiologically unstable infant with gastroschisis [15]. Indeed, the risk of mortality was increased only for those infants with SNAP-II scores greater than 28, a value far exceeding the average SNAP-II score of 8 observed in the patient population with gastroschisis used in this study [15].…”
Section: Discussionmentioning
confidence: 96%
“…Recently, the CAPSNet database used SNAP-II scoring to predict mortality in patients with gastroschisis [15]. This assessment, however, still required 12 hours of intensive hemodynamic, respiratory, and laboratory surveillance to calculate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment was considered to include a prenatal phase (prenatal diagnostic workup); an intrapartum phase, including obstetrical planning and actual intrapartum management; and a condition-specific phase of postnatal treatment. Reported risk factors included maternal (age, smoking, and drug use for GS) and neonatal criteria such as gestational age, birth weight, and Score for Neonatal Acute Physiology (SNAP-II) [6], a validated outcome predictor for both CDH and GS [7,8] …”
Section: Methodsmentioning
confidence: 99%